Legal Protection of Consumers in Online Buying and Selling according to Islamic Law and Consumer Protection Law - Resta Pratama Faudi; M. Junaidi (Universitas Muhammadiyah Surakarta, 2025)
The purpose of this research is to analyze how legal protection is obtained by consumers in online buying and selling. The legal protection analyzed is not only from the existing positive legal rules, but also from Islamic law. This research is motivated by the increasing number of online buying and selling models. Online shop itself is a term that emerged in the early 2000s regarding buying and selling systems based on the internet and applications. So, it is necessary for people who use online buying and selling to know the legal protection they get. The research method used is doctrinal normative research. The material studied is the laws and regulations. The rules are examined qualitatively to describe how legal protection is contained in the law. The results obtained in this study are that both in the rules of positive law and Islamic law it is found that consumers are protected. The legal protection obtained is both preventive and redressive. So that in the end, with this legal protection, both producers and consumers must and obey the existing regulations. So that the online buying and selling process is mutually beneficial to both parties, both producers and consumers.